Electron beam-based direct writing of nanostructures using a palladium β-ketoesterate complex - Jureddy, Chinmai Sai; Maćkosz, Krzysztof; Butrymowicz-Kubiak, Aleksandra; Szymańska, Iwona B.; Hoffmann, Patrik; Utke, Ivo (Beilstein Journal of Nanotechnology, 2025)
Gas-assisted focused electron beam-induced deposition (FEBID) as a direct, minimally invasive 3D nanopatterning tool offers many advantages in making nanostructures with complex shapes and novel compositions for evolving nanotechnological applications. In this work, structures were nanoprinted using a fluorine-free β-ketoesterate complex, bis(tert-butylacetoacetate)palladium(II), [Pd(tbaoac)2]. The internal nanostructure and composition of the deposits were determined, and possible volatile products produced under electron-induced dissociation, explaining the composition, are investigated. A method to eliminate the residual gas contamination during FEBID was implemented. [Pd(tbaoac)2] contains large organic ligands and only about 5 atom % palladium in the pristine molecule, yet the obtained palladium content in the deposits amounts to around 30 atom %. This translates to an exceptional removal efficiency of about 90% for the ligand-constituting elements carbon and oxygen through electron-induced dissociation and desorption mechanisms. Comparison with other precursors confirms that the β-ketoesterate family has the highest ligand removal percentage and constitutes thus an interesting model chemistry for further high-metal-content FEBID studies. The possibility of growing nanopillars makes this complex a promising precursor for nanoprinting 3D structures with finely focused electron beams.
Keywords: 3D nanoprinting; electron-induced molecule dissociation; focused electron beam-induced deposition; metal nanostructures; metalorganic complexes